(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
Wind energy is currently widely regarded as one of the most favorable green clean sources of energy. Several wind turbine principles with various generator architectures have been evolved to exchange the available wind energy into electric power. The DFIG partial Variable-Speed Wind Turbine (VSWT) system is most proper for wind turbine energy because of its numerous benefits over Fixed-Speed Wind Turbines (FSWT). This paper introduces a comparative review of the different wind turbine conversion energy and a valuable summary of the recent work in the literature on different Wind Energy Conversion Systems (WECS) of a DFIG modeling, Maximum Power Point (MPP), and the latest control system for operation. On the other side, comparisons and discussions between different wind turbines have been presented in the current study to be beneficial for research studies.